Non-systemic fungal endophytes in Festuca rubra plants infected by Epichloë festucae in subarctic habitats - Zabalgogeazcoa, Iñigo; Gundel, Pedro E.; Helander, Marjo (Fungal Diversity, 2013)
8 páginas, 2 tablas, 2 figuras. -- The final publication is available at www.springerlink.com Epichloë festucae is an endophytic fungus that infects systemically the aerial tissues of the host grass Festuca rubra. This fungus is transmitted vertically from the mother plant to seeds. Hypothetically, the presence of E. festucae could affect the infection of a plant by other fungal species. This could occur if E. festucae metabolites produced in planta interfere negatively with other fungal infections; or alternatively, if the modulation of plant defenses by the endophyte favour further fungal infections. We have analyzed the presence of culturable non-systemic endophytes in plants of F. rubra infected (E+) and not infected (E-) by E. festucae in two subarctic habitats, meadows and riverbanks in Northern Finland. The observed non-systemic endophyte infection frequencies were similar among E+ and E- plants from riverbanks, and E+ plants from meadows. In contrast to these, the infection frequency was significantly lower in E- plants from meadows. This result suggests that the presence of E. festucae is not a main factor determining the presence of non-systemic endophytes in plants. Instead, plant genetic characteristics related to compatibility with E. festucae and other endophytes in the more stable meadow populations might play a role in these fungus-fungus-plant interactions. As a result of the survey, 18 different taxa of non-systemic endophytes were identified in plants of F. rubra. All were ascomycetes except for one basidiomycete. Three endophytic taxa could not be ascribed to a genus, but sequence data indicated that they were conspecific with other unidentified endophytes that have been isolated in cold biomes at different locations. The research leading to these results has received funding from INTERACT (grant agreement No. 262693) under the European Community's Seventh Framework Programme, from Academy of Finland (Project No. 137909), and Spanish Government (Project AGL2011-22783) Peer reviewed